1996
DOI: 10.1074/jbc.271.39.23902
|View full text |Cite
|
Sign up to set email alerts
|

Partial Fusion Activity of Influenza Virus toward Liposomes and Erythrocyte Ghosts Is Distinct from Viral Inactivation

Abstract: Final extents of fusion of influenza virus (A/PR/8/34 strain) with neutral and partially acidic liposomes were monitored with (i) a fluorescence resonance energytransfer assay in which the liposomes were labeled and (ii) by the dequenching of octadecylrhodamine, initially incorporated in the viral membrane. The latter assay was also employed in the fusion of influenza virus and Sendai virus with erythrocyte ghosts. In all cases, a phenomenon of partial fusion activity of the virus was observed, which is distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…These results are reminiscent of results obtained for Sendai virus (28) and influenza virus (30) for which a phenomenon of partial fusion activity has also been described that was not due FIG. 4.…”
Section: Discussionsupporting
confidence: 80%
“…These results are reminiscent of results obtained for Sendai virus (28) and influenza virus (30) for which a phenomenon of partial fusion activity has also been described that was not due FIG. 4.…”
Section: Discussionsupporting
confidence: 80%
“…From these observations, we concluded that HA-receptor binding that is too tight interferes with the enlargement of fusion pores. Many studies have been published concerning the relationship between HA binding and fusion activities (1,7,12,13,15,20,21,23), and most indicate that the binding of HA to receptors is necessary for an efficient fusion reaction. The question is whether this concept is inconsistent with our conclusions from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion was monitored continuously at pH 5.0 using the fluorescence dequenching assay as described previously (8-10). In brief, fusion of influenza virus with a target membrane will result in R18 dilution into the new bilayer, which, in turn, will promote a release in probe selfquenching, and a concomitant increase in the fluorescence of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose fusion was followed by the octadecylrhodamine B chloride (R18) dequenching assay (8-10), using liposomes as target membranes for intact virions. In order to simulate the outer monolayer of a target cell plasma membrane these model membranes were composed of the zwitterionic phospholipids PC and PE, and also included the sialic acid-containing ganglioside GD1a, a molecule known to act as a receptor for the virus (10, 11, 15, 20). Two populations of liposomes were prepared: one encapsulating an aqueous medium at pH 7.4, and one encapsulating exactly the same medium, but with its pH adjusted to 5.0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation